E-LEARNING AND BEYOND: SHAPING THE MODERN EDUCATIONAL PROCESS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the impact of digitalization on the educational process, focusing on the rise of e-learning and its ongoing influence on modern education. It examines both the benefits and challenges of digital learning, highlights innovative technologies shaping the future, and discusses the evolving role of teachers and institutions. The article emphasizes the importance of balancing traditional and digital methods to create an inclusive and effective learning environment.